1998
DOI: 10.1161/01.hyp.31.5.1136
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices on Hypertension in a Country in Epidemiological Transition

Abstract: Abstract-Assessment of knowledge, attitudes, and practices (KAP) is a crucial element of hypertension control, but little information is available from developing countries where hypertension has lately been recognized as a major health problem. Therefore, we examined KAP on hypertension in a random sample of 1067 adults aged 25 to 64 years from the Seychelles Islands (Indian Ocean). KAP were assessed from an administered structured questionnaire. The age-standardized prevalence of hypertension (screening bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
63
1
4

Year Published

2000
2000
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 44 publications
10
63
1
4
Order By: Relevance
“…In the observational group p=0.0010*** (s), in the interventional group p=<0.0001*** (s). These results coincide with the Line Aubert et al 9 For Stroke patients KAP questionnaire consists of 23 questions for these questions answers were taken from the patients and significance was calculated, scores as follows (Figure 3 and 4). In the observational group p=0.0007*** (s).…”
Section: Discussionsupporting
confidence: 86%
“…In the observational group p=0.0010*** (s), in the interventional group p=<0.0001*** (s). These results coincide with the Line Aubert et al 9 For Stroke patients KAP questionnaire consists of 23 questions for these questions answers were taken from the patients and significance was calculated, scores as follows (Figure 3 and 4). In the observational group p=0.0007*** (s).…”
Section: Discussionsupporting
confidence: 86%
“…However, study done in India (Pragnesh, 2014) and Seychelles (Aubert et al, 1998) found that the majority had good knowledge and greater than 96% in Seychelles and 80.4%, India, of the participant knew that obesity was associated with hypertension, but in our study only 62.9% of the participant mentioned it as a risk factor. This discrepancy could be explained by the type of participant included in the study.…”
Section: Discussioncontrasting
confidence: 68%
“…6 Assessment of knowledge, attitudes, and practices (KAP) is a crucial element of hypertension control, but little information is available from developing countries where hypertension has lately been recognized as a major health problem. 7 Hypertension and its complications can be controlled by modifying lifestyle related risk factors, and generating awareness about these risk factors among hypertensive patients. So this study was planned to assess the life style pattern, knowledge, attitude and practices related to hypertension among diagnosed patients of hypertension attending a tertiary care hospital.…”
Section: Introductionmentioning
confidence: 99%